UJI ORGANOLEPTIK NUGGET AYAM DENGAN PENAMBAHAN BROKOLI (Brassica Oleracea var Italica) - Mahayani, Anak Agung Putu Sri; Cahyani, Wahyu Kanti Dwi; Saputra, Jefrianto (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2024)
This research involved 20 panelists with several nugget samples that had to be assessed. The samples are NA0 which is a control or chicken nugget without broccoli; NA1 is a chicken nugget with the addition of 10% broccoli; NA2 is a chicken nugget with the addition of 15% broccoli; and NA3 is a chicken nugget with the addition of 20% broccoli. The assessment that the panelists must carry out is to rate each sample with 5 ratings, namely very dislike, dislike, moderate, like, and very like. According to the results of the research based on taste, most of the panelists liked the chicken nugget treatment with the addition of 15% broccoli. For the color category, most of the panelists liked chicken nuggets with the addition of 10% - 20% broccoli. For the texture category, some panelists liked chicken nuggets with the addition of 15% broccoli. For the aroma category, most of the panelists liked chicken nuggets with the addition of 10% - 20% broccoli. Based on these four aspects, the addition of broccoli was 15%, and the control (without broccoli) was most popular with the panelists.